International journal of music education. (Sage, 1983)
Beginning with vol. 22 (2004), each of the three issues per volume has a special focus: the April issue focuses on "Research," the August issue, "Showcase" highlights topics of international interest, and the December issue, "Practice" deals with music teaching and learning at all age levels.